15 Improving equitable enrollment rates in pediatric remote patient monitoring programs. (30th November 2022) - Sump, Courtney; Denker, Kylee; Chapman, DaVona; White, Christine; Riddle, Sarah
Abstract : Background: Remote patient monitoring (RPM) is a form of telemedicine that transmits patient-generated health data to the healthcare team using technology. RPM may detect health problems sooner, breakdown communication barriers, and permit more frequent changes to care plans. Our institution manages 300 patients/month in 14 RPM programs. Lack of specific inclusion criteria and lack of enrollment analysis allows for disparities in who is offered RPM. Objectives: To Increase percent of eligible patients enrolled in RPM from 83% to 95% by June 2022. Methods: Our interdisciplinary team, including a nurse, physician, quality specialist, data analyst, and family members, aimed to improve RPM enrollment. Using the model for improvement, a high-level process map was developed, as well as a key driver diagram ( figure 1 ). Key drivers included process ownership, clear RPM inclusion criteria, family buy-in, and transparency of enrollment data. Interventions included creating program specific process maps, developing inclusion criteria for new programs, standardizing family communication, and monthly feedback to teams on enrollment successes/failures. Enrollment of eligible patients was tracked on an annotated run chart to assess the effect of our interventions over time. Secondary measures included family satisfaction. Results: Through our interventions, we increased the median percentage of eligible patients enrolled in RPM from 83% to 91% ( figure 2 ). The most common failure of enrollment was due to caregivers with limited English proficiency ( figure 3 ). Family satisfaction was high with 98% caregivers agreeing they would recommend RPM to others. Conclusions: Using QI methods allowed us to increase the percent of eligible patients we enroll in RPM programs at our institution. Next steps include 1) creation of a workflow that allows enrollment of patients with limited English proficiency, and 2) improving adherence with a family-centered focus to meet the needs of our patients.